Ketidakefektifan ICOC dalam Mengatasi Potensi Ancaman di Luar Angkasa - Meirizal, Ade (Jurnal Ilmu Hubungan Internasional LINO, 2022)
as collective initiation from major countries in Europe, ICoC or International Code of Conduct on Outer Space was launched in 2008. This code of conduct is expected to call the main actors in space activity with more concern about space security, cooperation, and anti-space militarization activities. However, there are many interpretations in each country and make this code of conduct not effective. In recent decades, a lot of space missions launched to LEO and GEO have produced a million debris. Moreover, security dilemmas in each actor bring them to traditional security competition. The US, China, and Russia officially reform the Space Force to strengthen their space capability. Worstly, this force is armed with high-tech space technology such as Satellite for military operations, satellite jamming and so on. This research will mention various ineffectiveness of ICoC, limited in space debris production and militarization of outer space by major actors on the global level.